(untitled) (Polis (Santiago), 2018)
Different arguments are held when it refers to Complex Thinking; but the offer diminishes when we want to imagine which are the caracteristics that the subject which is the support for this epistemology must have. This article deals with the caracteristics of the subject of Complexity, considering this as an emergence of a theoretical transdisciplinary model – which is also presented in this text-. In this proposition, the exercise of reflexivity favours the access to metacognitions which predispose the subject to a kind of conviviency based on a ‘planetary conscience’.